Intertemporal solvency of Turkey's current account - Ayla Oğuş Binatlı; Niloufer Sohrabji (Izmir University of Economics, Department of Economics, 2008)
We test for sustainability of Turkey's current account position between 1992 and 2007 using the intertemporal solvency model of Hakkio and Rush (1991) and Husted (1992). This approach examines the relationship between exports and imports+ (which include imports, net interest and unilateral transfer payments). Cointegration between inflows and outflows implies that the intertemporal budget constraint is satisfied. We use the Johansen and the Gregory and Hansen (1996) cointegration tests to determine linkages between exports and imports+ in Turkey. Using the Johansen test we find no cointegration and thus reject intertemporal solvency of the current account for this period. If we allow for a structural break in the cointegrating relation using the Gregory Hansen procedure we do find evidence of cointegration between the two series. This result can be used to estimate the long-run relationship between exports and imports+ using dynamic OLS and test for weak and strong sustainability of the current account position. We find evidence for weak sustainability but reject strong sustainability of the Turkish current account position in recent years.
Keywords: F32; F41; 330; Current account sustainability; intertemporal budget constraint; Turkey; cointegration; Leistungsbilanz; Außenwirtschaftliches Gleichgewicht; Intertemporale Allokation; Türkei